Association of Opioid Usage with Spinal Cord Stimulation Outcomes. Issue 4 (13th December 2017) - Sharan, Ashwini D; Riley, Jonathan; Falowski, Steven; Pope, Jason E; Connolly, Allison T; Karst, Edward; Dalal, Nirav; Provenzano, David A
Abstract: Study Design: Observational study using insurance claims. Objective: To quantify opioid usage leading up to spinal cord stimulation (SCS) and the potential impact on outcomes of SCS. Setting: SCS is an interventional therapy that often follows opioid usage in the care continuum for chronic pain. Methods: This study identified SCS patients using the Truven Health MarketScan databases from January 2010 to December 2014. The index event was the first occurrence of a permanent SCS implant. Indicators of opioid usage at implant were daily morphine equivalent dose (MED), number of unique pain drug classes, and diagnosis code for opioid abuse. System explant was used as a measure of ineffective SCS therapy. Multivariate logistic regression was used to analyze the effect of pre-implant medications on explants. Results: A total of 5, 476 patients (56 ± 14 years; 60% female) were included. SCS system removal occurred in 390 patients (7.1%) in the year after implant. Number of drug classes (odds ratio [OR] = 1.11, P  = 0.007) and MED level (5–90 vs < 5 mg/d: OR = 1.32, P  = 0.043; ≥90 vs < 5 mg/d: OR = 1.57, P  = 0.005) were independently predictive of system explant. Over the year before implant, MED increased in 54% (stayed the same in 21%, decreased in 25%) of patients who continued with SCS and increased in 53% (stayed the same in 20%, decreased in 27%) of explant patients ( P  = 0.772). Over the year after implant, significantly more patients with continued SCS had an MED decrease (47%) or stayed the same (23%) than before ( P  < 0.001). Conclusions: Chronic pain patients receive escalating opioid dosage prior to SCS implant, and high-dose opioid usage is associated with an increased risk of explant. Neuromodulation can stabilize or decrease opioid usage. Earlier consideration of SCS before escalated opioid usage has the potential to improve outcomes in complex chronic pain.